STRUCTURAL BEHAVIOR OF COMPOSITE SLABS SUBJECTED TO IMPACT LOADING - Ibrahim Aziz, Khalil; Mohammed suwaid, Hashim (Anbar Journal of Engineering Sciences, 2017)
This paper presents the experimental results of composite slabs under static and impact loading. Total of six specimens classified one specimen test under static loading and the remaining five were tests under impact dynamic loading with different parameters as type of connections and degree of interaction of composite slab. Low - velocity impact test was adopted by select the falling mass (4 kg) made from steel material and formed as ball shape without nose. The ball dropped freely from height of (2.4 m) and strikes the top of composite slab. The designed dimensions of specimens is (500×500×60 mm) as reinforced concrete slab that reinforced by mesh of (RBC) and the steel plate is (3 mm) in thickness. Deflection due to first crack is recorded, number of blows caused first crack and failure were counted. The test results showed that the welded stud connectors gives high strength capacity and resistance under static and impact dynamic loadings than other than type of connections, also, full interaction as degree of interaction is better than others